Development of Motion Graphics As Social Studies Learning Media on Indische Partij Material - Miftakhul Umi Nadziru; Agung Wiradimadja (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACT Social studies learning activities in general still do not take advantage of the use of technology-based learning media because of the limited number and type of media as well as the limited ability of the teacher. The learning media used by teachers is still textual in nature, that is, it only comes from textbooks so that it makes students' interest and motivation in learning social studies, especially historical material, to be low. To overcome these problems, developed innovative technology-based learning media, namely motion graphics. The aim of this research is developing motion graphics teaching media and testing the feasibility of IPS teaching media on Indische Partij material. The method used in this study uses an R&D approach with the ADDIE model. The product trial process was carried out in class VIII SMP PGRI 1 Kesamben. ADDIE's stages for developing teaching media include 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluate. The feasibility test results from the expert validator show a percentage of 95.45%. for material validation, 90.62% for language validation, and 95.45% for media validation. While the test results on students obtained an average value of 89.10%. Based on these averages it can be stated that motion graphics products as social studies learning media are "very feasible" to be used in learning activities and can be disseminated without going through revisions. Keywords: motion graphics media, Indische Partij, social studies learning